2021
DOI: 10.5005/jp-journals-10071-23828
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Clinical Risk-scoring Algorithm for Scrub Typhus Severity in South India

Abstract: A bstract Background A clinical risk-scoring algorithm (CRSA) to forecast the scrub typhus severity was developed from two general hospitals in Thailand where patients were classified into three groups—nonsevere, severe, and fatal. In this study, an attempt was made to validate the risk-scoring algorithm for prognostication of scrub typhus severity in India. Materials and methods This prospective study was conducted at a hospital in South Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The authors have reported an improved prediction of severity: approximately 77% of cases were correctly classified as severe [47]. An algorithm to differentiate scrub typhus from dengue has been described by Mitra et al, by using the variables of oxygen saturation, total white blood cell count, haemoglobin, total bilirubin, serum glutamic/ oxaloacetic transaminase (aspartate aminotransferase), and altered sensorium.…”
Section: Scoring System For Diagnosismentioning
confidence: 99%
“…The authors have reported an improved prediction of severity: approximately 77% of cases were correctly classified as severe [47]. An algorithm to differentiate scrub typhus from dengue has been described by Mitra et al, by using the variables of oxygen saturation, total white blood cell count, haemoglobin, total bilirubin, serum glutamic/ oxaloacetic transaminase (aspartate aminotransferase), and altered sensorium.…”
Section: Scoring System For Diagnosismentioning
confidence: 99%
“…It is an acute zoonotic infection caused by a mite-borne bacterium called Orientia tsutsugamushi, which is transmitted via insect bites [3] . The arthropod responsible for this transmission, which also serves as a reservoir for this bacterium, is the Leptotrombidium mite [4][5][6][7][8] . O. tsutsugamushi is a Gram negative, obligate, intracellular organism [4,7] .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence and clinical profile of ST have not been studied in depth in southern Indian states like Tamil Nadu. Clinically, ST manifests as high fever with malaise, headache, cough, myalgia, exanthematous rash, and lymphadenopathy along with the involvement of different systems, such as the respiratory, cardiovascular, and hepatobiliary systems as well as the brain [3,6,9] . This leads to manifestations like hepatitis, pneumonia, renal failure, septic shock, myocarditis, acute respiratory distress syndrome (ARDS), and multiple organ dysfunction syndrome (MODS) [3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation